2001
DOI: 10.1016/s0014-5793(01)02243-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the fatty acid elongation 1 gene are associated with a loss of β‐ketoacyl‐CoA synthase activity in low erucic acid rapeseed

Abstract: Low erucic acid rapeseed (LEAR) is characterised by a near absence of very long chain fatty acids in the seed oil which has been correlated with a lack of acyl-CoA elongation activity. Here we show that the absence of acyl-CoA and ATP-dependent elongation activities in microsomes isolated from LEAR embryos is associated with an absence of L L-ketoacyl-CoA synthase activity encoded by the Bn-fatty acid elongation 1 (FAE1) genes. Size exclusion chromatography of solubilised microsomes revealed the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…In B. napus, SNP/indel mutations in the coding region of the FAE1 resulted in loss-of-function alleles (Han et al, 2001;Roscoe et al, 2001;Katavic et al, 2002;Wu et al, 2007Wu et al, , 2008. In contrast, the loss-of-function FAE1 allele e in yellow mustard was caused by an insertional disruption in its coding region by Sal-PIF, a PIF/ Harbinger-like DNA transposon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In B. napus, SNP/indel mutations in the coding region of the FAE1 resulted in loss-of-function alleles (Han et al, 2001;Roscoe et al, 2001;Katavic et al, 2002;Wu et al, 2007Wu et al, , 2008. In contrast, the loss-of-function FAE1 allele e in yellow mustard was caused by an insertional disruption in its coding region by Sal-PIF, a PIF/ Harbinger-like DNA transposon.…”
Section: Discussionmentioning
confidence: 99%
“…In the FAE1 gene from the A genome of B. napus, a single base change of nucleotide 845 from cytosine to thymine resulted in a loss-of-function allele (Han et al, 2001;Roscoe et al, 2001;Katavic et al, 2002;Wu et al, 2007Wu et al, , 2008. A second mutation consisting of a 4-bp deletion between T1366 and G1369 in the FAE1 gene, which led to a frameshift mutation, was predominantly found in the C genome (Wu et al, 2007(Wu et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins solubilized from HEAR membranes revealed, as expected, a high-molecular mass fraction characteristic of the acyl-CoA elongase complex associated with the 3-hydroxyacyl-CoA dehydratase and able to elongate C18:1-CoA to C20:1 and C22:1. In contrast, chromatography of solubilized proteins from the LEAR microsomal fraction revealed an absence of condensing and elongation activities and the presence of one peak of 3-hydroxy acyl-CoA dehydratase activity at a low molecular mass; this led to the assumption that an acyl-CoA elongase complex is not present in LEAR [8]. By the same token, the presence of 3-ketoacyl-CoA synthase appears to be essential to allow the formation of the acyl-CoA elongase complex.…”
Section: The Brassica Napus Acyl-coa Elongase Is a Multienzyme Complexmentioning
confidence: 95%
“…This low content in VLCFA has been correlated with a lack of acyl-CoA elongation activity [10]. Roscoe et al [8] have shown that this absence in LEAR microsomes is associated with a lack of 3-ketoacyl-CoA synthase activity.…”
Section: The Brassica Napus Acyl-coa Elongase Is a Multienzyme Complexmentioning
confidence: 99%
See 1 more Smart Citation